The Impact of Assistive Technology on Autism Spectrum Disorder: A Systematic Review - Bollin, Angela; VanderMolen, Julia; Bierwagen, Taylor (Journal of the American Academy of Special Education Professionals, 2018)
The purpose of this research was to review the assistive technology (AT) specific assessment models and instruments that have been developed for children with Autism Spectrum Disorder (ASD) in order to provide an overview of the strategies to be employed in rehabilitation and education. Three electronic databases were searched for peer-reviewed studies investigating children with Autism Spectrum Disorder (ASD) and the use of assistive technology to assist with speech difficulties, little social interaction, and poor motor skills. Relevant studies were independently reviewed and appraised by three reviewers. Methodological quality was quantified using the American Speech-Language-Hearing Association’s levels of evidence. In total, 21 studies were included in the review. We argue that there is a need to develop a more thorough guide for AT professionals in the process of AT assessment for children with Autism Spectrum Disorder.